Current situation’s analysis of the problem in intensive care of complicated community-acquired pneumonias in children - Horodkova, Yu. V.; Городкова, Юлія Вячеславівна (My University, 2020)
INTRODUCTION: The leading place in the nosological structure of pathology in the lower respiratory tract is pneumonia. Community-acquired pneumonia (CAP) remains one of the most common causes of childhood morbidity and accounts for about 16% of all deaths in children under 5 years old. The article presents a review of publications of recent years using the databases PubMed, Scopus, Web of Science, Google Scholar regarding the current possibilities of intensive care of complicated community-acquired pneumonia (CCAP), problems of using extracorporeal detoxication methods (ECDM), the choice of starting antibacterial therapy and microbiological monitoring and the problem of determining the severity of endogenous intoxication syndrome in children with CCAP. PURPOSE: To analyze the relevance of intensive therapy in children with complicated community-acquired pneumonia, to consider current therapeutic interventions and the need to use extracorporeal detoxication methods in complex treatment based on the analysis of scientific literature data. CONCLUSIONS: The epidemiology of community-acquired pneumonia is currently characterized by an increasing trend in morbidity and mortality worldwide. Plasmapheresis is not first-line therapy, because antibacterial drug (ABD), conservative detoxication, respiratory support are the mainstay of treatment like for other infections, but in case of CCAP the course of basic therapy is often not enough and then there is a need for ECDM. Identification of causative microorganisms in children with CCAP remains a constant problem. In most cases, therapy is prescribed empirically and knowledge of local epidemiology, the structure of ABD resistance is an important platform for improving antibacterial therapy. The optimal therapeutic approach for CCAP remains open to research.
https://orcid.org/0000-0001-5954-7682
Keywords: plasmapheresis; pneumonia; child; intensive care units